2019
DOI: 10.3390/ijms20205019
|View full text |Cite
|
Sign up to set email alerts
|

Directed Evolution of an Improved Rubisco; In Vitro Analyses to Decipher Fact from Fiction

Abstract: Inaccuracies in biochemically characterizing the amount and CO2-fixing properties of the photosynthetic enzyme Ribulose-1,5-bisphosphate (RuBP) carboxylase/oxygenase continue to hamper an accurate evaluation of Rubisco mutants selected by directed evolution. Here, we outline an analytical pipeline for accurately quantifying Rubisco content and kinetics that averts the misinterpretation of directed evolution outcomes. Our study utilizes a new T7-promoter regulated Rubisco Dependent Escherichia coli (RDE3) scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 58 publications
1
51
1
Order By: Relevance
“…Third, multiple efforts to improve the rate of rubisco carboxylation have made limited progress (Mueller-Cajar et al, 2007;Gomez-Fernandez et al, 2018;. Cases where some increase in the net carboxylation capacity of rubisco was achieved (via directed evolution) include only form-I and form-III isoforms (Wilson et al, 2016;Zhou & Whitney, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Third, multiple efforts to improve the rate of rubisco carboxylation have made limited progress (Mueller-Cajar et al, 2007;Gomez-Fernandez et al, 2018;. Cases where some increase in the net carboxylation capacity of rubisco was achieved (via directed evolution) include only form-I and form-III isoforms (Wilson et al, 2016;Zhou & Whitney, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Escherichia coli has long been the preferred host for the directed evolution of Rubisco for the sake of enhancing carboxylation activity toward CO 2 due to its high transformation efficiency and simple genetic tools ( Mueller-Cajar and Whitney, 2008a ). Several screening platforms for directed evolution of Rubisco have been developed by coupling cell growth to Rubisco activity ( Parikh et al, 2006 ; Mueller-Cajar et al, 2007 ; Mueller-Cajar and Whitney, 2008b ; Cai et al, 2014 ; Wilson et al, 2016 ; Zhou and Whitney, 2019 ). Unfortunately, affinity and catalytic efficiency toward CO 2 failed to synchronously increase ( Kubis and Bar-Even, 2019 ).…”
Section: Natural Co 2 Fixation Pathwaysmentioning
confidence: 99%
“…Accordingly, it should be feasible in the current synthetic biology revolution to circumvent these evolutionary barriers to RuBisCO adaptation. Indeed, promising steps toward this goal have been already demonstrated using directed evolution of the enzyme to generate variants with improved catalytic traits in non-photosynthetic archaea (Wilson, Alonso and Whitney, 2016) and plant-like Form I hexadecameric RuBisCO from photosynthetic bacteria (Zhou and Whitney, 2019) and cyanobacteria (Wilson et al , 2018). Thus, these findings presented here provide optimism for engineering RuBisCO in food, fibre and fuel crops to have improved catalytic efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…First, a recent analysis of the correlative nature of RuBisCO kinetics has demonstrated that associations between kinetic traits are weakened when a large number of species are considered (Flamholz et al , 2019; Iñiguez et al , 2020). Further, engineering efforts to alter RuBisCO kinetics have produced enzyme variants that deviate from proposed catalytic trade-offs between S C/O , k catC and K C (Wilson et al , 2018; Zhou and Whitney, 2019). Thus together, these results indicate that RuBisCO kinetic traits are perhaps not as inextricably linked as originally thought, and suggest that there is scope for increasing the catalytic efficiency of the enzyme as has happened in nature for RuBisCO in some red algae (Andersson and Backlund, 2008).…”
Section: Introductionmentioning
confidence: 99%